Students' awareness of the tripartite accounting in Bowen University, Iwo. Issue 2 (5th October 2015) - Oladele, Femi
Abstract : Purpose: – The purpose of this paper is to assess Nigerian students' level of awareness of the tripartite accounting (TA), unmask the ills of the propaganda for professional practice as the core of the accounting profession and emphasise the TA. Awareness of the fact that the frontiers of accounting is increasingly expanding beyond professional practice is inchoate in Nigeria. The role of accounting extends further to research and policy formulations for governments and corporate organisations, as it assumes a multi-dimensional sine qua non for reporting, budgeting and budgetary control, environmental impact measurement, forensics and other socio-political and economic policy measures. Design/methodology/approach: – Questionnaires were administered to 100 final-year students from the Department of Accounting in Bowen University, Iwo. Findings: – There is unilateral stereotype of the profession always tending to practice as the core of the accounting profession; there is little awareness of the benefits of undertaking research and/or policy-based accounting, limiting students' focus to becoming only professional practitioners, which results in low number of senior academics in the field of Accounting evident in most tertiary institutions and the evident inadequacies of Nigeria's standards-setting and policy-making systems and mechanisms. Originality/value: – Tertiary institutions should be the "place of orientation" for the TA, nurturing and developing students' interest, hence, the strong proposal for balancing TA through clamour for institutional interrelationship to ensure effectiveness, efficiency, progress and sustainability of the profession.